2014
DOI: 10.1002/ejic.201402312
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)‐Coordinated α‐Azophenols: Effect of the Metal‐Ion Geometry on Phenoxyl/Phenolate Oxidation Potential and Reactivity

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…In agreement with the implications of the XRD‐derived structure, the absorption maximum in the reflectance mode at 607 nm indicated a distorted square pyramidal or nearly square‐planar coordination sphere . Similar conclusions hold for the spectra in solution, in which the recorded maximum at λ =610 nm falls between data typical of square‐planar (555 nm< λ <575 nm) and square‐pyramidal coordination (620 nm< λ <675 nm).…”
Section: Resultssupporting
confidence: 80%
“…In agreement with the implications of the XRD‐derived structure, the absorption maximum in the reflectance mode at 607 nm indicated a distorted square pyramidal or nearly square‐planar coordination sphere . Similar conclusions hold for the spectra in solution, in which the recorded maximum at λ =610 nm falls between data typical of square‐planar (555 nm< λ <575 nm) and square‐pyramidal coordination (620 nm< λ <675 nm).…”
Section: Resultssupporting
confidence: 80%
“…The starting compounds of 2-methylquinolin-8-amine [ 24 ], and 7-methylquinolin-8-amine [ 25 ] were prepared using the reported methods. 4-Amino- N -(5-methylisoxazol-3-yl)benzenesulfonamide ( I ), 4-amino- N -(pyridin-2-yl)benzenesulfonamide ( II ), 4-amino- N -(pyrimidin-2-yl)benzenesulfonamide ( III ), 4-amino- N -(4-methylpyrimidin-2-yl)benzenesulfonamide ( IV ), 4-amino- N -(4,6-dimethylpyrimidin-2-yl)benzenesulfonamide ( V ), 4-amino- N -(2,6-dimethoxypyrimidin-4-yl)benzenesulfonamide ( VI ), and 4-amino- N -(6-methoxypyridazin-3-yl)benzenesulfonamide ( VII ) were commercially available.…”
Section: Methodsmentioning
confidence: 99%
“…Benisvy et al reported a number of complexes of pyrazole/imidazole-phenolate with Cu, Co or Zn [11][12][13][14][15][16]. Kochem et al reported [18] a system highlighting the effect of steric strain in the Cu complex on the phenolate/phenoxyl oxidation process.…”
Section: Introductionmentioning
confidence: 96%